2003
DOI: 10.1097/01.wcb.0000087342.31689.18
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Ischemic Brain Damage by Nitrous Oxide and Xenon

Abstract: Neuronal death after ischemia-induced brain damage depends largely upon the activation of the N-methyl-D-aspartate (NMDA) excitatory glutamate receptor that is a target for many putative neuroprotective agents. Whereas the NMDA receptors mediate ischemic brain damage, blocking them is deleterious in humans. Here, the authors investigated whether nitrous oxide or xenon, which are gaseous anesthetics with a remarkably safe clinical profile that have been recently demonstrated as effective inhibitors of the NMDA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
103
3
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 31 publications
11
103
3
4
Order By: Relevance
“…Additionally, other studies have shown that xenon provides neuroprotection in different preclinical models. Xenon has shown protection in different types of models; an oxygen-glucose deprived neuronal-glial coculture cell model (35), a middle cerebral artery occlusion rat model (36) and a cardiac arrest pig model (37). Hence, our study findings may be transferable to wider clinical applications.…”
Section: Discussionmentioning
confidence: 81%
“…Additionally, other studies have shown that xenon provides neuroprotection in different preclinical models. Xenon has shown protection in different types of models; an oxygen-glucose deprived neuronal-glial coculture cell model (35), a middle cerebral artery occlusion rat model (36) and a cardiac arrest pig model (37). Hence, our study findings may be transferable to wider clinical applications.…”
Section: Discussionmentioning
confidence: 81%
“…Gases have thus the great advantages to present a reducing risk of neurotoxic side effects, compared to chemical neuroprotective drugs, especially at the low concentrations used for neuroprotection. Nitrous oxide and xenon reduce ischemic neuronal death in an in-vivo model of transient cerebral ischemia in rats and decrease the NMDA-induced Ca 2+ influx on neuronal cell cultures studied by in-vitro calcium video microscopy (David et al, 2003). These two gases produce the same effect than memantine, a low-affinity antagonist of NMDA receptor which is already used in clinics for neurodegenerative disease treatments (David et al, 2006).…”
mentioning
confidence: 86%
“…If we compared these data with in-vivo pharmacology studies, we noticed that this ratio corresponded to the ratio of the narcotic potency of xenon compared to nitrous oxide (about 1.38) as estimated by the concentration of gas necessary to induce loss of righting reflex in rodents (Koblin et al, 1998;David et al, 2003), considered to be a behavioural endpoint closely related to MAC-awake (Campagna et al, 2003). In comparison, the ratio of gas-induced volume expansion for xenon and nitrous oxide in annexin V, a protein which could be considered as a prototype of NMDA receptor for its properties of ion selectivity and voltage gating (Demange et al, 1994), did not correspond to the ratio of anesthetic potency of xenon and nitrous oxide.…”
Section: Determination Of Crystallographic Structures Of Proteins Undmentioning
confidence: 99%
“…Furthermore, N 2 O (70% N 2 O/30% oxygen) failed to alter infarct size or behavioral outcomes as assessed at 3 or 14 days after transient middle cerebral artery occlusion (MCAO) and as compared with 70% nitrogen/30% oxygen treatment (Yokoo et al, 2004). While N 2 O administration (3 h) delivered after transient focal cerebral ischemia can improve cortical histopathology in rat (Abraini et al, 2005;David et al, 2003), N 2 O administered after global brain ischemia in paralyzed, ventilated primates failed to improve outcome even when administered for 48 h after the initial insult (Gisvold et al, 1984). These results are perhaps explained by the recent observation that even short-term high concentration (hyperbaric) N 2 O exposure (r3 h) in nonischemic, adult rat brain produces reversible neuronal injury, and prolonged N 2 O exposure ( > 3 h) causes neuronal cell death (Jetovic-Todorovic et al, 2003).…”
Section: Nitrous Oxidementioning
confidence: 99%